Multi-parametric investigations on gravitational vortex hydropower system (GVHPS) using computational hydrodynamic analysis: a verified computational procedure-based investigation. (26th January 2023) - Raja, Vijayanandh; Raji, Arul Prakash; AL-bonsrulah, Hussein A Z; Ramaiah, Manivel; Ahmed, Ali Mahmood; Rajendran, Parvathy; Murugesan, Ramesh; Mathaiyan, Vijayakumar; Al-Bahrani, Mohammed
Abstract: The use of energy resources has been critical to the advancement of human civilization. Finding a reliable energy source is one of the most difficult tasks of the 21st century. Natural gas, coal and other conventional energy sources have hastened the industrialization and modernization of several countries. However, there is widespread concern that the release of carbon dioxide into the atmosphere from these traditional sources is the leading cause of climate change. Increased pollution, flooding, drought, rising sea levels, high temperatures and other effects of climate change have a significant impact on the environment. As a result, current research is focusing on renewable and sustainable energy sources. Hydro energy is a low-cost and environmentally friendly way to generate electricity. Even still, the vast majority of hydroelectric energy remains underutilized. Hydrostatic and hydrodynamic methods are the two most common approaches for extracting energy from water. The gravitational vortex hydropower (GVHP) with hydro rotor is one such renewable turbine. By routing the water into a GVHP basin, which generates a water vortex on its inside surface while it runs, the mechanical energy of free-flowing water is converted to kinetic energy in this GVHP. The major goal of this study is to investigate the flow field characteristics of a GVHP numerically for various geometrical variables such as basin diameter, cone angle and notch angle. CATIA is used to create several geometric models, which are then simulated using a commercial computational fluid dynamics application. Different geometric factors of conical basin design were studied using computational hydrodynamic analysis, and their impacts on vortex generation and tangential velocity in the study region are recorded. The maximum tangential velocity derived from different basin geometry can be used to forecast the performance of the GVHP. Finally, the optimized GVHP along with its dimensions, such as a cone angle of 14°, a notch angle of 13° and a basin diameter of 1000 mm, are found out and suggested for real-time applications.